FOOD SECURITY IN EAST JAVA DURING THE COVID-19 PANDEMIC: EVIDENCE FROM RICE PRODUCTION, RAINFALL, AND HUMAN DEVELOPMENT INDICATORS - Muljaningsih, Sri; Ekawaty, Marlina (Journal of Indonesian Applied Economics, 2025)
Purpose This study aims to examine the determinants of food security in East Java Province during the COVID-19 pandemic, focusing on climate-related and socioeconomic factors. Design/methodology/approach This study employs a quantitative approach using multiple linear regression estimated through the Ordinary Least Squares (OLS) method. The dependent variable is the food security index in East Java Province. The independent variables include climate-related indicators, namely rainfall and rice production, and socioeconomic indicators associated with the pandemic context, including life expectancy, expected years of schooling, and real per capita expenditure. East Java was selected because it was Indonesia’s leading rice-producing province in 2020, a year marked by major socioeconomic disruption caused by COVID-19. Findings The findings show that rice production, life expectancy, and real per capita expenditure positively affect food security in East Java. These results indicate that agricultural productivity, health conditions, and household purchasing power play important roles in strengthening regional food security. Meanwhile, rainfall and expected years of schooling have no significant effect on the food security index, suggesting that these variables may not directly influence food security in the short-term context of 2020. Research limitations/implications This study is limited to East Java Province and focuses only on 2020. Future research may use panel data across several years or compare multiple provinces to capture broader food security dynamics. Originality/value This study provides context-specific evidence on how climate-related and socioeconomic factors shaped food security in East Java during the COVID-19 pandemic.